Conserved spike protein in Avastroviruses: A potential factor in cross-species transmission - Yong Wang; Aolin Li; Hongfu Ma; Yankun Lan; Jiaguo Wang; Xin Wang; Liang Zhao; Qifei Wu; Xu Guo (Poultry Science)
Avastroviruses (AAstVs) are important pathogens in avian species, with cross-species transmission being a critical factor in their evolutionary dynamics. The spike protein encoded by the ORF2 region plays a central role in viral entry and is believed to influence host range and transmission across species. This study analyzed the evolutionary conservation and divergence of spike proteins across different AAstV strains. Using sequence alignments, structural predictions via AlphaFold 2, and protein structure comparisons, we found significant structural conservation, particularly in β-sheet regions, despite originating from different hosts. Ancestral state reconstruction using BEAST 2.7 traced AAstVs back to a common ancestor from around 780 AD, with host-jumping events contributing to the formation of distinct viral groups. The conserved spike protein structures support the hypothesis that spike similarity plays a crucial role in cross-species transmission. Our findings highlight the crucial role of spike protein conservation in enabling AAstV to infect multiple host species, providing insights into the molecular mechanisms of host adaptation and viral evolution, and future studies will aim to experimentally validate the role of spike proteins in cross-species transmission.